Students' Character Building through the Implementation of School Discipline in SMAK Santo Petrus Kewapante - Martina Rita Yuklina; Yuliana Mazing; Rinceana Pawe (UM Purwokerto Press, 2025)
Character Building of Students Through the Implementation of School Discipline at SMAK Santo Petrus Kewapante. THESIS. Faculty of Teacher Training and Education. Muhammadiyah University of Maumere. 2025. This study aims to describe how the Implementation of Discipline and Order in SMAK Santo Petrus Kewapante plays a role in the formation of student character. The characters in question include discipline, responsibility, obedience to rules, and polite and religious attitudes. This study was conducted with a qualitative descriptive approach, using observation, interview, and documentation techniques. The results of the study showed that the implementation of school regulations, such as time regulations, use of appropriate uniforms, environmental cleanliness, and joint prayer activities, significantly contributed to the formation of student character. However, its implementation still faces challenges, such as low student awareness, lack of involvement of some teachers, and minimal support from parents. However, through good cooperation between teachers, schools, and students, the implementation of discipline can be improved effectively so that the formation of student character can run more optimally.